Absenteeism : age, sex and job satisfaction (a case study in Kim Hin Industry Berhad) - Lo, Kim Seng (Universiti Malaysia Sarawak, (UNIMAS), 1997)
The present study has three objectives: a) to examine the relationship between age and avoidable absenteeism frequency; b) to determine sex differences in avoidable absenteeism frequency; and c) to identify the relationship of job satisfaction and employees' avoidable absenteeism frequency. Three hypotheses are drawn for this study to meet these objectives. The data, collected from a ceramics manufacturing company were analyzed using Statistical Package for Social Sciences (SPSS). The results indicated that there was no relationship between age and absence frequency; so with job satisfaction of workers; but male workers were identified to be more frequently absent than female workers.